2016
DOI: 10.5606/archrheumatol.2016.5849
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Thoracic Ultrasonography in the Evaluation of the Severity of Pulmonary Involvement in Patients With Systemic Sclerosis

Abstract: Objectives: This study aims to investigate the effectiveness of thoracic ultrasonography (USG) in a single session in the evaluation of the severity of pulmonary involvement in systemic sclerosis. Patients and methods: A total of 48 consecutive systemic sclerosis patients (2 males, 46 females; mean age 50.8±11.9 years; range 21 to 76 years) followed-up in our center were included. A thoracic USG using a linear probe was performed for each patient to evaluate the parenchymal involvement by two pulmonary disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 15 publications
0
27
0
1
Order By: Relevance
“…Cakir et al also reported B-lines negatively correlated with DLCO (r = −0.56; p = 0.0001) and FVC (r = 0.46; p = 0.001) [39]. In another study, Tardella et al, after evaluating 14 lung intercostal spaces in patients with SSc, detected that a cutoff = 10 B-lines was predictive for HRCT presence in significant SSc-ILD patients, and they confirmed correlations with HRCT (rho = 0.819; p < 0.001), DLCO (rho = 0.600; p < 0.001), and with health-related quality of life variables (rho = 0.560; p < 0.001) [32].…”
Section: Discussionmentioning
confidence: 99%
“…Cakir et al also reported B-lines negatively correlated with DLCO (r = −0.56; p = 0.0001) and FVC (r = 0.46; p = 0.001) [39]. In another study, Tardella et al, after evaluating 14 lung intercostal spaces in patients with SSc, detected that a cutoff = 10 B-lines was predictive for HRCT presence in significant SSc-ILD patients, and they confirmed correlations with HRCT (rho = 0.819; p < 0.001), DLCO (rho = 0.600; p < 0.001), and with health-related quality of life variables (rho = 0.560; p < 0.001) [32].…”
Section: Discussionmentioning
confidence: 99%
“…For the posterior chest, they selected the eighth LIS on three lines, namely the paravertebral, the subscapular, and the posterior axillary lines. Among the reasons for choosing these LIS were the demonstrated higher prevalence rate of B-lines in these fields and the ease of evaluation by LUS [14, 29]. To the best of our knowledge, there is no meta-analysis about which LIS should be evaluated in a modified LUS for diagnosis of CTD-ILD.…”
Section: Discussionmentioning
confidence: 99%
“…42 Our current approach to the assessment of SSc-ILD, which includes plain chest radiography, pulmonary auscultation and pulmonary function tests (PFT), is insensitive to detect early ILD. Therefore, as an effort to fulfil this gap, many authors have proposed LUS as an imaging technique that is able to assess SSc-ILD, 43–60 even in the earliest stages. 49,51…”
Section: Lungmentioning
confidence: 99%
“…During this phase, an efficient screening tool should be extensively used to early detect lung abnormalities, which may be confirmed by HRCT, to start early a target treatment. Despite many technical differences (convex/linear and 2.5–10 MHz probes; scanning protocols considering 72–10 intercostal spaces; scoring systems; pathological B-lines cut-off), 4350,53–60 LUS provides significant positive correlations between B-lines and HRCT findings and, less commonly, between B-lines and vascular damage (capillaroscopic pattern and number of digital ulcers). 45,50 Literature data also describe a similar correlation between pleural line alterations (‘US’ thickness > 3 mm or irregularities) and HRCT, probably allowing a better discrimination than B-lines in ILD detection.…”
Section: Lungmentioning
confidence: 99%
See 1 more Smart Citation